Attitudes and Associated Factors towards Care for Dying Patients among Non-Palliative Care Nurses, Yogyakarta, Indonesia - Huriah, Titih; Hidayah, Nurul; Mikami, Akichika (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: The increment of terminal health problems causes the demand for palliative care to increase. Nurses’ attitudes toward palliative care have critical implications on the quality of care for terminally ill patients. This study aimed to investigate non-palliative care nurses’ attitudes towards death and dying patients in palliative care in Indonesia.Method: A cross-sectional design was performed in four general hospitals, five primary health centers, and three nursing homes in Yogyakarta. Systematic random sampling was the method employed. The research instrument used Frommelt Attitudes towards Care of the Dying (FATCOD). FATCOD is a 30-item tool using a five-point Likert scale to indicate respondents' attitudes toward caring for dying patients. Attitudes had two categories, namely favorable (≥ mean score of the total score of (FATCOD) Scale) and unfavorable ( mean score of the total score of (FATCOD) Scale). Two hundred seventeen (217) non-palliative care nurses completed the FATCOD and a ten-item demographic questionnaire. The data analysis used descriptive statistics, chi-square, and linear regression.Results: The total FATCOD score achieved in this study was 111.29±9.44 (range 30–150). Concerning nurses’ attitudes towards the family members of terminally ill dying patients, the score was 39.85 (±4.12) out of a possible 50. Besides attitudes towards patient care provision, the score was 71.43 (±6.39) out of a possible 100. The nurses' attitudes towards the dying patients showed that the favorable and unfavorable attitudes had almost the same percentage. Of significance, working experience variables were associated with attitudes in the total FATCOD and patient FATCOD. Working experience and level of education were related to attitudes towards the family FATCOD.Conclusion: Non-palliative care nurses had a favorable attitude towards palliative care. The ministry of health should give awareness by providing various training, workshop, formal and informal education about PC for nurses.